Influence of Perceived Time and Entrepreneurial Skills Constraints on Entrepreneurship Interest among Final Year Undergraduate and Honours Students at the University of Fort Hare - Manzi, Bongile; Aderibigbe, John K.; Chimucheka, Tendai (Journal of Reviews on Global Economics, 2019)
Several scholarly efforts have been previously exerted in investigating student entrepreneurship interest in the developed countries, and several studies have contributed in this direction, yet little was achieved in South Africa. The main aim of this study was to empirically assess perceived time and entrepreneurial skills constraints as possible barriers to entrepreneurial interest among a sample of 366 (205 (56%) male and 161 (46%) female) final year undergraduate and postgraduate ‘honours' students of a previously disadvantaged university in the Eastern Cape Province of South Africa, using the survey research design, and a structured validated questionnaire. Three hypotheses were stated and tested using Multiple Regression Analysis. The results revealed that perceived time and entrepreneurial skills constraints jointly influenced entrepreneurship interest, F (2, 363) = 25.887; R2 = 0.120; p<. 01. The results further revealed that perceived time constraint independently influenced entrepreneurship interest, (β = 0.226; t= 4.108; p< .01). Likewise, the results showed that entrepreneurial skills constraint independently influenced entrepreneurship interest, (β = 0.188; t= 3.415; p< .01). The findings are valuable to the policy makers and professionals in promoting the spirit of entrepreneurship among the youth, with the consequence decline rate of joblessness.